PENGEMBANGAN MANUSIA SEBAGAI SUMBER BELAJAR PADA BERBAGAI JENJANG PENDIDIKAN - Zeky, Muhammad (Program Studi PAI STAI Al Falah Banjarbaru, 2022)
Abstract: This study aims to find out how the true nature of humans as a source of learning and how to develop human beings as a source of learning at various levels of education. The type of research chosen in this study is library research using qualitative methods. The data used is secondary data, namely data that is not obtained directly from the source. The results of this study indicate that humans as learning resources mean making humans as seekers, savers, processors and presenters of messages who are able to provide experience and understanding in learning and help achieve the desired learning goals in accordance with expectations. In the world of education, the role of humans as a source of learning is focused on the figure of the teacher who becomes the facilitator and main source of learning. Then, human development as a learning resource must be adjusted to the existing level of education, where at the elementary school level the teacher as a learning resource must create a stimulus response, a sense of security, comfort, and a memorable learning experience in the minds of students. At the junior high school level, teachers must begin to provide learning through a creative and interactive environment, experience, and technology. At the high school level, teachers must maximize the use of technology, the internet, and digital libraries in which they present a variety of creativity that can support the learning development of students. In addition, teachers must also avoid delivering monotonous subject matter, weak voices, and not daring to make eye contact because it can reduce students' trust in teachers. At the tertiary level, human development as a learning resource is becoming more varied, where the orientation is not only limited to teachers or lecturers, but can also be in the form of speakers in seminars, discussion forums, and the use of Learning Resource Centers and the internet are increasingly being encouraged. Keywords: Education Level, Human, Learning Resources. Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana sebenarnya hakikat dari manusia sebagai sumber belajar serta bagaimana pengembangan manusia sebagai sumber belajar pada berbagai jenjang pendidikan. Jenis penelitian yang dipilih pada penelitian ini adalah penelitian kepustakaan dengan menggunakan metode kualitatif. Data yang digunakan adalah data sekunder, yaitu data yang tidak didapat langsung dari sumbernya. Hasil dari penelitian ini menunjukan bahwa manusia sebagai sumber belajar berarti menjadikan manusia sebagai pencari, penyimpan, pengolah dan penyaji pesan yang mampu memberikan pengalaman dan pemahaman dalam belajar serta membantu tercapainya tujuan pembelajaran yang diinginkan sesuai dengan harapan. Dalam dunia pendidikan, peran manusia sebagai sumber belajar tertuju pada sosok guru yang menjadi fasilitator dan sumber belajar utama. Kemudian, pengembangan manusia sebagai sumber belajar harus disesuaikan dengan jenjang pendidikan yang ada, dimana pada jenjang SD guru sebagai sumber belajar harus menciptakan stimulus respon, rasa aman, nyaman, dan pengalaman belajar yang berkesan di benak peserta didik. Pada jenjang SMP, guru harus mulai memberikan pembelajaran melalui lingkungan, pengalaman, serta teknologi yang bersifat kreatif dan interaktif. Pada jenjang SMA, guru harus lebih memaksimalkan pemanfaatan teknologi, internet, dan perpustakaan digital yang di dalamnya meyajikan berbagai kreatifitas yang mampu menunjang perkembangan belajar peserta didik. Selain itu, guru juga harus menghindari penyampaian materi pelajaran yang monoton, suara yang lemah, dan tidak berani melakukan kontak mata karena dapat mengurangi kepercayaan peserta didik terhadap guru. Pada jenjang perguruan tinggi, pengembangan manusia sebagai sumber belajar menjadi semakin variatif, dimana orientasinya bukan hanya sebatas guru atau dosen saja, tetapi juga bisa berupa pembicara dalam seminar, forum diskusi, serta penggunaan Pusat Sumber Belajar dan internet yang semakin digalakkan. Kata Kunci : Jenjang Pendidikan, Manusia, Sumber Belajar.